Odpowiedź :
Odpowiedź:
[tex]x \in (-\infty,2) \cup (3,\infty)[/tex]
Szczegółowe wyjaśnienie:
[tex]$f(x)=\frac{1}{\sqrt{x^{2}-5x+6} }[/tex]
Dziedzina:
[tex]x^{2}-5x+6>0[/tex]
[tex]\Delta=25-4 \cdot 1 \cdot 6=1[/tex]
[tex]$x_{1}=\frac{5-1}{2} =2 \vee x_{2}=\frac{5+1}{2}=3[/tex]
[tex](x-2)(x-3)>0[/tex]
[tex]x \in (-\infty,2) \cup (3,\infty)[/tex]
[tex]\begin{gathered}\sqrt{x^2-5x+6}\not=0 \wedge x^2-5x+6\geq0\\\Downarrow\\x^2-5x+6>0\\\end[/tex]
[tex]x^2-5x+6>0\\x^2-2x-3x+6>0\\x(x-2)-3(x-2)>0\\(x-3)(x-2)>0\\x\in(-\infty,2)\cup(3,\infty)\\\\\boxed{D:x\in(-\infty,2)\cup(3,\infty)}[/tex]